TINJAUAN YURIDIS PENYELENGGARAAN BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN DI KOTA SEMARANG - Harlita Harlita (Yayasan Akrab Pekanbaru, 2019)
The Social Security Organizing Agency (BPJS) is one of the Institutions that is responsible for labor issues that organizes workforce social security programs, to protect workers and their families from the threat of work risks in this case workers outside the work relationship or independent labor. The method used is a sociological juridical analytical descriptive research specification. Data obtained through observation, interviews and literature studies. The data is then analyzed by qualitative methods. The results of this study indicate (1) The implementation of a workforce social security program that carries out work outside the employment relationship is basically one of the instruments in terms of social security of workers and improvement of welfare and has been carried out in accordance with applicable laws and regulations (2) in the implementation of social security program activities workers who carry out work outside of work relations are influenced by several obstacles both from the Social Security Organizing Agency (BPJS) and from the independent workforce.